The victim’s right to waiva the complaint - Adnan, Salma; Naser, Allaa (Journal of Legal Sciences, 2022)
Intervention in the criminal case requires examining the evidence examining the identity of the accused, and preparing him with all the necessary elements to issuing the verdict, and in view of the procedures that this research takes, which may extend for a long time, thinking has turned toward dealing with the criminal case without the criminal judiciary, and this call has escalated with the trend to give the victim an important role in politics criminal justice until it become a real party in criminal justice and in light of that, the recognition of the important role that can be played by the individuals desire to achieve criminal justice, which led to the development of this justice and in light of this development, the only goal of criminal justice is no longer punishment , but it has become the achievement of protection of the private rights of individuals and refome the relationship between the victim and the accused is an important goal in this development and in this context and away from the courts of law, the criminal case is terminated by his own will form the victim alone and that by relinquishing his complaint.